First record of subgenus Corynopus Lepeletier and Brullé, 1835 (Genus Rhopalum Stephens, Hymenoptera: Crabronidae: Crabronini) from India: a new species and a key to Asian species of the subgenus - Saini, Varun; Dey, Debjani (Zootaxa, 2024)
The subgenus Corynopus Lepeletier de Saint Fargeau and Brullé, 1835 of the genus Rhopalum Stephens, 1829 is recorded for the first time from India. A new species, viz., Rhopalum (Corynopus) chettalicum, (India: Karnataka) is described. A key and the checklist of all Asian species of the subgenus Corynopus are provided.